The Effect of Annealing Temperature on the Optical Properties of the a-Ge: As Thin Films - Khdayer, I.H. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
a-Ge: As thin films have prepared by thermal evaporation teclmique, then they were annealing at various temperatures within the range (373-473) K. The result of X-ray di ffraction spectrum was showing that all the specimens remained in amorphous structure before and after annealing process. This paper studied the effect of annealing temperature as a function of wavelength on the optical energy gap and optical constants for the a-Ge:As thin films . Results have showed that there was an increasing in the optical energy gap Egopt) values with the in ,;rcasing of the annealing temperatures within the range of measurements due to the decrease in defect states near the bands. The refraction index , real and imaginary parts of dielectric constant and the extinction coefficient decrease with the i.ncrellsing of the annealing temperatnres .